2001
DOI: 10.1021/jp011997a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Studies of Hydrofluorocarbons in Faujasite-type Zeolites:  Modeling Guest-Induced Cation Migration in Dry Zeolites

Abstract: We have developed and applied a new force field for simultaneously modeling the dynamics of hydrofluorocarbons (HFCs) and exchangeable Na cations in faujasite-type zeolites. Our aim is to account for (i) the zeolite's capacity of separating HFC isomers, (ii) the experimentally observed unusual cation migration in Na−Y from the β-cages into the supercages upon the adsorption of HFCs, and (iii) the abnormal trans/gauche ratio in these systems. Energy minimizations and molecular dynamics simulations performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 80 publications
6
63
0
Order By: Relevance
“…On the other hand, the possibility of weak interactions of the C-H bonds of nitriles with other oxygen atoms exposed in the cavity (like proposed to occur for hydrocholorocarbons in Nafaujasites [44]), should not cause a decrease in the CN stretching frequency. Taking into account that the cations may displace a little bit upon adsorption of different molecules, the possibility of the formation of adsorbed species where two different cations interact with the N lone pair and with a p-type orbital seems to be possible on NaX.…”
Section: ''Unusual'' Low Frequency Nitrile Adsorbed Speciesmentioning
confidence: 97%
“…On the other hand, the possibility of weak interactions of the C-H bonds of nitriles with other oxygen atoms exposed in the cavity (like proposed to occur for hydrocholorocarbons in Nafaujasites [44]), should not cause a decrease in the CN stretching frequency. Taking into account that the cations may displace a little bit upon adsorption of different molecules, the possibility of the formation of adsorbed species where two different cations interact with the N lone pair and with a p-type orbital seems to be possible on NaX.…”
Section: ''Unusual'' Low Frequency Nitrile Adsorbed Speciesmentioning
confidence: 97%
“…In a previous molecular dynamics (MD) study devoted to hydrated zeolite 4A, Faux [16] observed a relatively slow motion of some of the Na + ions (one order of magnitude slower than the water diffusion in the same system). Using the same type of method, Jaramillo et al [17] also observed the diffusion of some of the cations in a model of NaX upon adsorption of two polar hydrofluorocarbons. Standard molecular dynamics is obviously not well-suited for studying equilibrium cation distributions (and redistributions), since cation diffusion takes place on a timescale which is larger (or comparable) to the MD timescale.…”
mentioning
confidence: 99%
“…The cation force field has been adapted from the work of Jaramillo and Auerbach (Jaramillo et al, 2001). The cation-framework potential consists of an exp-6 repulsion-dispersion term that acts between the cation and the oxygen atoms of the faujasite and a Coulombic term that acts between the cation and both the oxygen and T atoms of the framework.…”
Section: Models and Methodsmentioning
confidence: 99%